Metal-organic framework derived crystalline nanocarbon for Fenton-like reaction - Lian, Tingting (2024)
Nanoporous carbons with tailorable nanoscale texture and long-range ordered structure are promising candidates for energy, environmental and catalytic applications, while the current synthetic methods do not allow elaborate control of local structure. Here we report a salt-assisted strategy to obtain crystalline nanocarbon from direct carbonization of metal-organic frameworks (MOFs). The crystalline product maintains a highly ordered two-dimensional (2D) stacking mode and substantially differs from the traditional weakly ordered patterns of nanoporous carbons upon high-temperature pyrolysis. The MOF-derived crystalline nanocarbon (MCC) comes with a high level of nitrogen and oxygen terminating the 2D layers and shows an impressive performance as a carbocatalyst in Fenton-like reaction for water purification. The successful preparation of MCC illustrates the possibility to discover other crystalline heteroatom-doped carbon phases starting from correctly designed organic precursors and appropriate templating reactions.